The Intellectual and Political Landscape of Iran Before and After the 1979 Revolution: A conversation with Michail Theodosiadis - Namazi, Rasoul (Dia-noesis: A Journal of Philosophy, 2025)
Iran has undergone a turbulent intellectual trajectory since 1979. The Revolution was launched and carried to victory with the participation of diverse intellectual currents whose influence decisively shaped the post-1979 landscape. Although heterogeneous, many of these currents leaned to the left. Across much of the world at the time, Marxism set the dominant terms of debate, and Iran was no exception. Numerous leading literary and intellectual figures were Marxists or shared left-leaning convictions. Even Islamist thinkers drew selectively on Marxist concepts and vocabulary to formulate their understanding of Islam and their political project. Different strands—Islamic Marxism, Soviet-style orthodoxy, Maoism, and various forms of Third-Worldism—competed before and during the Revolution and left a lasting imprint on the formation of the Islamic Republic.